Tuning CO2 reduction selectivity via structural doping of TiO2 photocatalysts - Hana Kmentová; Miroslava Filip Edelmannová; Zdeněk Baďura; Radek Zbořil; Lucie Obalová; Štěpán Kment; Kamila Kočí (Journal of CO2 Utilization)
This study explores the effects of various structural dopants on TiO₂ to enhance selectivity of reaction products in photocatalytic CO₂ reduction. Specifically, the impacts of nitrogen doping, platinum surface doping, and self-doping with Ti³ ⁺ ions (via oxygen vacancies in reduced TiO₂-x) were investigated. X-ray diffraction confirmed the anatase phase, with crystal sizes ranging from 24 to 27 nm. High-resolution transmission electron microscopy revealed uniformly distributed active sites on platinum-doped TiO₂ surfaces. Nitrogen doping selectively stabilized oxygen vacancies, enhancing CO production, while platinum loading acted as an electron trap, improving charge separation and promoting the deeper reduction of CO₂ to CH₄. Self-doping with Ti³ ⁺ ions introduced structural defects that further influenced photocatalytic dynamics. X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses demonstrated how these dopants reorganize surface defects, thereby fine-tuning product selectivity. Variations in dopant-to-oxygen ratios and smaller crystallites led to different yields of CO and CH₄, emphasizing the importance of dopant type and distribution. Stability tests confirmed consistent photocatalytic activity across multiple cycles, highlighting the robustness and reusability of the modified materials. This study provides valuable insights into the interplay between dopants, crystal structure, and photocatalytic performance, offering new directions for the design of tailored catalysts for selective CO₂ reduction.